Graphene modified coating as well as preparation method and application thereof
Through graphene modified coating technology, edge graphene oxide nanosheets and modified epoxy resins are used to solve the problems of high cost and reduced corrosion resistance of traditional zinc-rich primers, and low-cost and efficient corrosion resistance are achieved.
Patent Information
- Application Number
- CN202411707248.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
AI Technical Summary
Traditional zinc-rich primer has reduced anticorrosion performance and high material cost due to the high cost of zinc powder and oxidative expansion effects.
Graphene-modified coatings are used to improve dispersion ability through edge graphene oxide nanosheets, reduce the amount of zinc powder, and maintain the cathodic protection function of zinc powder, and improve the corrosion resistance of the resin through graphene-modified epoxy resin.
It achieves low-cost anti-corrosion performance improvement, extends the cathode protection function time of zinc powder, enhances the density of the paint film and the utilization rate of the paint, and reduces the construction consumption and the unit price of the paint.
Smart Images

Figure CN119529628A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coatings, and in particular relates to a graphene-modified coating and a preparation method and application thereof. Background Art
[0002] Zinc-rich paint is the first choice for anti-rust primer because it is rich in zinc powder and has a cathodic protection effect on the steel substrate. Zinc-rich primer is widely used in the anti-corrosion of steel structures, but zinc powder is a non-renewable resource. The amount of zinc powder added must be ≥65% to be called "zinc-rich primer", and its specific gravity is >2.2Kg / L. Therefore, the material cost and construction cost of zinc-rich primer are very high.
[0003] The premise for zinc powder to achieve "cathodic protection" in the paint film is that each zinc powder particle can be connected to each other to form a conductive "circuit" to ensure its anti-corrosion performance. When all the electrons of the zinc powder particles are transferred or the conductive path is interrupted, the "cathodic protection" function of the zinc powder is declared invalid, and due to the oxidation reaction of the zinc powder itself, the zinc salt formed will absorb water and "expand" its particle volume, forming more and larger corrosion "pathways" and "inducing nodes", resulting in the destruction of the density of the paint film, thereby accelerating the spread of corrosion.
[0004] In summary, in the traditional "zinc-rich primer" technology, the premise for achieving good anti-corrosion performance is the "accumulation" and "close contact" of a large amount of zinc powder, which leads to the high cost of zinc-rich primer; in addition, during the service life of the paint film, the zinc powder will destroy the dense structure of the paint film due to its own oxidation "expansion" effect, thereby weakening the anti-corrosion performance of the primer. Summary of the invention
[0005] In view of this, the object of the present invention is to provide a graphene-modified coating and a preparation method and application thereof. The graphene-modified coating provided by the present invention has low cost and excellent anti-corrosion performance when used as a primer.
[0006] In order to achieve the above object, the present invention provides the following scheme:
[0007] The present invention provides a graphene modified coating, comprising a component A and a component B; based on the mass of the graphene modified coating being 100%, the component A comprises:
[0008]
[0009]
[0010] Taking the mass of the graphene modified coating as 100%, the component B comprises:
[0011] Water-based epoxy resin 15-20%;
[0012] Water 1-3%;
[0013] The second auxiliary agent is 1.19-2.7%;
[0014] The mass ratio of component A to component B is (3-5):1.
[0015] Preferably, the method for preparing the edge oxide graphene nanosheets comprises the following steps:
[0016] Mixing a binder, an organic solvent and a single-layer graphene to prepare a graphene electrode sheet;
[0017] The graphene electrode sheet is subjected to electrolytic oxidation modification to obtain the edge oxide graphene nanosheet.
[0018] Preferably, based on 100% of the mass of the graphene modified coating, the first auxiliary agent includes 5-10% of the auxiliary solvent and 0.5-1.5% of the anti-settling agent; the total mass of the alcohol solvent and the first auxiliary agent is 9.5-20%.
[0019] Preferably, based on the mass of the graphene modified coating as 100%, the second auxiliary agent includes 0.5-1% dispersant, 0.5-1% wetting agent, 0.1-0.5% defoaming agent, 0.02-0.05% pH regulator, 0.02-0.05% bactericide, and 0.05-0.1% thickener.
[0020] Preferably, the total mass of the water and the second auxiliary agent is 2.29-5%.
[0021] Preferably, the waterborne epoxy curing agent includes a polyamide curing agent and / or a fatty amine curing agent; and the waterborne epoxy resin includes E20 waterborne epoxy resin.
[0022] The present invention provides a method for preparing the graphene-modified coating according to the above scheme, comprising the following steps:
[0023] Mixing a water-based epoxy curing agent, edge-oxidized graphene nanosheets, zinc powder, barium sulfate, a pigment, an alcohol solvent and a first auxiliary agent, and performing a first dispersion to obtain a dispersion material;
[0024] Sand-grinding the dispersed material to obtain component A;
[0025] Mixing a waterborne epoxy resin, water and a second auxiliary agent, and performing a second dispersion to obtain a B component;
[0026] The component A and the component B are mixed to obtain the graphene modified coating; the mass ratio of the component A to the component B is (3-5):1.
[0027] Preferably, the rotation speed of the first dispersion starts from 300 r / min, gradually increases to 1500 r / min, and then is maintained at 1500 r / min for 30 to 60 min.
[0028] Preferably, the second dispersion speed starts from 200 r / min, gradually increases to 600 r / min, and then is maintained at 600 r / min for 10 to 30 min.
[0029] The present invention provides the use of the graphene-modified coating described in the above scheme or the graphene-modified coating prepared by the preparation method described in the above scheme in primer.
[0030] The present invention provides a graphene modified coating, comprising component A and component B; based on the mass of the graphene modified coating being 100%, the component A comprises: 4-5% of waterborne epoxy curing agent; 1-6% of edge oxidized graphene nanosheets; 20-50% of zinc powder; 15-45% of barium sulfate; 1-5% of pigment; 3-10% of alcohol solvent; 5.5-11.5% of a first auxiliary agent; based on the mass of the graphene modified coating being 100%, the component B comprises: 15-20% of waterborne epoxy resin; 1-3% of water; 1.19-2.7% of a second auxiliary agent; the mass ratio of the component A to the component B is (3-5):1. The edge oxidized graphene nanosheets provided by the present invention modify the graphene plane edge sites with oxygen-containing functional groups through electrochemical selective oxidation, thereby improving the dispersibility of graphene in a solvent. The graphene modified coating provided by the present invention has a reduced amount of zinc powder, but the cathodic protection function provided by the zinc powder will not be reduced under the action of graphene, and the density of the paint film is increased under the action of graphene (by adding graphene, the amount of zinc powder is reduced, the expansion "points" are reduced, and the structural density of the paint film is improved), thereby increasing the difficulty of corrosive media invading the paint film and the substrate, and therefore, the anti-corrosion performance is enhanced; under the same process film thickness, the salt spray test time is extended by 50 to 100% compared with the coating in the prior art, further indicating that the anti-corrosion performance is improved.
[0031] The cost of the graphene-modified coating provided by the present invention is reduced: the addition of graphene replaces 20-40wt.% of zinc powder, and under the same anti-corrosion performance requirements, the process film thickness is matched and reduced from 50μm to 30μm or from 30μm to 20μm. Therefore, the unit price of the coating and the construction consumption are reduced in both directions.
[0032] The graphene-modified coating provided by the present invention improves the bonding force between the resin and the zinc powder, thereby improving the cohesive force of the coating itself. During the construction process, under the same spraying process parameters, the rebound and scattering of the paint mist are reduced, and under the same process film thickness, the coating consumption is reduced, that is, the coating utilization rate is increased by 3 to 10% compared with similar competing products.
[0033] Compared with the prior art, the present invention solves the problem that graphene is easy to agglomerate and difficult to disperse evenly in the coating, and at the same time improves and enhances the corrosion resistance of the resin itself in the coating. First, relying on the conductivity of graphene, the connection between zinc powders in the coating is enhanced, effectively extending the time for zinc powders to provide cathodic protection; second, the corrosion resistance of the epoxy resin modified by graphene is enhanced. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0035] Figure 1 The anti-corrosion performance results of primers with different zinc powder ratios (the zinc-rich paint content in the primer is 40-100wt.%) at test times of 120h and 240h;
[0036] Figure 2 The anti-corrosion performance results of primers with different zinc powder ratios (0-30wt.% zinc-rich paint content in the primer) at test times of 120h and 240h;
[0037] Figure 3 The anti-corrosion performance results of primers with different zinc powder ratios (the zinc-rich paint content in the primer is 80-100wt.%) at test times of 480h and 720h;
[0038] Figure 4 The anti-corrosion performance results of primers with different zinc powder ratios (0-70wt.% zinc-rich paint content in the primer) at test times of 480h and 720h;
[0039] Figure 5 The salt spray comparison test chart of the pickled plate and the sandblasted plate when the test time was 120h, 240h, 480h and 720h respectively. DETAILED DESCRIPTION
[0040] The present invention provides a graphene modified coating, comprising a component A and a component B; based on the mass of the graphene modified coating being 100%, the component A comprises:
[0041]
[0042] Taking the mass of the graphene modified coating as 100%, the component B comprises:
[0043] Water-based epoxy resin 15-20%;
[0044] Water 1-3%;
[0045] The second auxiliary agent is 1.19-2.7%;
[0046] The mass ratio of component A to component B is (3-5):1.
[0047] Unless otherwise specified, the materials and equipment used in the present invention are commercially available products.
[0048] Component A will be described below.
[0049] Based on the mass of the graphene modified coating as 100%, the component A of the graphene modified coating provided by the present invention comprises 4-5% waterborne epoxy curing agent, preferably 4.2-4.8%. In the present invention, the waterborne epoxy curing agent preferably comprises a polyamide curing agent and / or a fatty amine curing agent.
[0050] Taking the mass of the graphene modified coating as 100%, the component A of the graphene modified coating provided by the present invention comprises 1-6% edge oxidized graphene nanosheets, preferably 2-4%. In the present invention, the method for preparing the edge oxidized graphene nanosheets preferably comprises the following steps: mixing a binder, an organic solvent and a monolayer graphene to prepare a graphene electrode sheet; and performing electrolytic oxidation modification on the graphene electrode sheet to obtain the edge oxidized graphene nanosheets.
[0051] In the present invention, the mixing of the binder, the organic solvent and the single-layer graphene preferably includes: homogenizing at a rotation speed of 300 rpm for 60 s, then homogenizing at a rotation speed of 2000 rpm for 600 s, and then homogenizing at a rotation speed of 300 rpm for 60 s.
[0052] In the present invention, the binder preferably includes polyvinylidene fluoride; the organic solvent preferably includes N-methylpyrrolidone; the single-layer graphene preferably includes single-layer graphene powder, and the thickness of the single-layer graphene is preferably 0.334nm. In the present invention, the mass of the binder is 9% of the mass of the single-layer graphene; the volume ratio of the mass of the single-layer graphene to the organic solvent is preferably 1g:1mL.
[0053] After the mixing is completed, the present invention preferably places the obtained mixed slurry in a mold for drying. In the present invention, the mold is preferably a cubic mold. In the present invention, the drying temperature is preferably 70° C. and the drying time is preferably 12 hours. The present invention can prepare an electrolytic electrode sheet (i.e., a graphene electrode sheet) with a fixed morphology by drying, which will fall off (scatter by itself) before electrolysis if it is not dried.
[0054] In the present invention, the current density of the electrolytic oxidation modification is preferably 30 mA·cm -2The frequency of the ultra-low frequency AC power is preferably 0.017 Hz, the electrolyte is preferably potassium bicarbonate solution, and the time is preferably 24 h; the concentration of the electrolyte is preferably 0.2 mol·L -1 .
[0055] In the present invention, the edge oxidized graphene nanosheets are preferably single-layer edge oxidized graphene nanosheets.
[0056] The edge oxidized graphene nanosheet provided by the present invention modifies the edge sites of the graphene plane with oxygen-containing functional groups through electrochemical selective oxidation, thereby improving the dispersion ability of graphene in a solvent; the edge oxidized graphene nanosheet is formed by oxidation and peeling off from the main body of the graphene electrode sheet through electrolytic oxidation modification, and the edge oxidized graphene nanosheet does not contain a binder.
[0057] Taking the mass of the graphene modified coating as 100%, the component A of the graphene modified coating provided by the present invention comprises 20 to 50% zinc powder, preferably 25 to 45%, and more preferably 30 to 40%.
[0058] Taking the mass of the graphene-modified coating as 100%, the component A of the graphene-modified coating provided by the present invention comprises 15 to 45% of barium sulfate, preferably 20 to 40%, and more preferably 25 to 35%.
[0059] Based on the mass of the graphene modified coating being 100%, the component A of the graphene modified coating provided by the present invention comprises 1-5% pigment, preferably 2-4%. In the present invention, the pigment preferably comprises one or more of iron red, aluminum phosphate and phosphoric acid.
[0060] Based on the mass of the graphene modified coating being 100%, the component A of the graphene modified coating provided by the present invention comprises 3-10% of an alcohol solvent, preferably 4-8%. In the present invention, the alcohol solvent preferably comprises ethanol.
[0061] Taking the mass of the graphene-modified coating as 100%, the component A of the graphene-modified coating provided by the present invention comprises 5.5 to 11.5% of the first auxiliary agent, preferably 6 to 10%.
[0062] Based on 100% of the mass of the graphene modified coating, the first auxiliary agent preferably includes 5-10% of the auxiliary solvent, and more preferably 6-8%; in the present invention, the auxiliary solvent preferably includes one or more of methyl ether, butyl ether and acetate.
[0063] Based on the mass of the graphene modified coating being 100%, the first auxiliary agent preferably includes 0.5 to 1.5% of the anti-settling agent, and more preferably 0.8 to 1.2%. In the present invention, the anti-settling agent preferably includes fumed silica. In the present invention, the total mass of the alcohol solvent and the first auxiliary agent is preferably 9.5 to 20%, and more preferably 10 to 15%.
[0064] Next, component B will be described.
[0065] Taking the mass of the graphene modified coating as 100%, the B component of the graphene modified coating provided by the present invention comprises 15-20% waterborne epoxy resin, preferably 16-18%. In the present invention, the waterborne epoxy resin preferably comprises E20 waterborne epoxy resin. In the present invention, the mass ratio of the waterborne epoxy resin to the waterborne epoxy curing agent is preferably (3-5):1, and more preferably (3.5-4.5):1.
[0066] Taking the mass of the graphene modified coating as 100%, the component B of the graphene modified coating provided by the present invention comprises 1 to 3% water, preferably 1.5 to 2.5%.
[0067] Taking the mass of the graphene modified coating as 100%, the component B of the graphene modified coating provided by the present invention includes 1.19 to 2.7% of the second auxiliary agent, preferably 1.4 to 2.5%.
[0068] Based on 100% of the mass of the graphene modified coating, the second auxiliary agent preferably includes 0.5-1% dispersant, preferably 0.6-0.8%. In the present invention, the dispersant preferably includes BYK 190 dispersant.
[0069] Based on 100% of the mass of the graphene modified coating, the second auxiliary agent preferably includes 0.5-1% of a wetting agent, preferably 0.6-0.8%. In the present invention, the wetting agent preferably includes BYK 349 wetting agent.
[0070] Based on 100% of the mass of the graphene modified coating, the second auxiliary agent preferably includes 0.1-0.5% defoamer, preferably 0.2-0.4%. In the present invention, the defoamer preferably includes BYK 024 defoamer.
[0071] Based on 100% of the mass of the graphene modified coating, the second auxiliary agent preferably includes 0.02-0.05% pH regulator, preferably 0.03-0.04%. In the present invention, the pH regulator preferably includes ammonia water, and the mass concentration of the ammonia water is preferably 0.03-0.04%.
[0072] Based on the mass of the graphene modified coating being 100%, the second auxiliary agent preferably includes 0.02-0.05% fungicide, preferably 0.03-0.04%. In the present invention, the fungicide preferably includes Dow KATHON(TM) LXE Kathon.
[0073] Based on the mass of the graphene modified coating being 100%, the second auxiliary agent preferably includes 0.05 to 0.1 parts of a thickener, preferably 0.06 to 0.08%. In the present invention, the thickener preferably includes Dow RM-8W and / or Dow RM-12W. In the present invention, the total mass of the water and the second auxiliary agent is preferably 2.29 to 5%, more preferably 3 to 4.5%.
[0074] In the present invention, the mass ratio of the component A to the component B is preferably (3-5):1, and more preferably (3.5-4.5):1.
[0075] The graphene modified coating provided by the present invention has a reduced amount of zinc powder, but the cathodic protection function provided by the zinc powder will not be reduced under the action of graphene, and the density of the paint film is increased under the action of graphene (by adding graphene, the amount of zinc powder is reduced, the expansion "points" are reduced, and the structural density of the paint film is improved), thereby increasing the difficulty of corrosive media invading the paint film and the substrate, and therefore, the anti-corrosion performance is enhanced; under the same process film thickness, the salt spray test time is extended by 50 to 100% compared with the coating in the prior art, further indicating that the anti-corrosion performance is improved.
[0076] The cost of the graphene-modified coating provided by the present invention is reduced: the addition of graphene replaces 20-40wt.% of zinc powder, and under the same anti-corrosion performance requirements, the process film thickness is matched and reduced from 50μm to 30μm or from 30μm to 20μm. Therefore, the unit price of the coating and the construction consumption are reduced in both directions.
[0077] The graphene-modified coating provided by the present invention improves the "wrapping" effect of the resin on zinc powder through graphene-modified epoxy resin, thereby enhancing the bonding force between the resin and the zinc powder, and further improving the cohesion of the coating itself. During the construction process, under the same spraying process parameters, the rebound and scattering of the paint mist are reduced, and under the same process film thickness, the coating consumption is reduced, that is, the coating utilization rate is increased by 3 to 10% compared with similar competing products.
[0078] The present invention prepares edge oxidized graphene nanosheets with polar edges and non-polar planes by selectively oxidizing and modifying the edge of monolayer graphene through low current density and ultra-low frequency electrolysis method. The amount of oxygen free radicals generated by the electrolyte is regulated by adjusting the current density and frequency of the applied alternating current. A small amount of oxygen free radicals will preferentially react from the relatively active parts of the edge binding energy of the monolayer graphene. The lower current density and shorter electrolysis time cause the generated oxygen free radicals to stop at the carbonyl photoenergy group for the edge oxidation degree of graphene, and are not enough to further oxidize to the carboxyl functional group. Therefore, there is only a weak hydrogen bonding force in the aqueous phase system to avoid the esterification reaction between the graphene oxides, thereby agglomerating and being difficult to disperse again. At the same time, the edge modification of graphene avoids the performance loss phenomenon caused by the self-condensation of a large number of oxidized functional groups in the conventional graphene oxide plane in the aqueous phase, and ensures the excellent water phase dispersibility of the edge oxidized graphene nanosheets and the excellent physical properties of the graphene itself. Compared with the existing technology, this paper solves the problem that conventional graphene is not dispersed in aqueous solution, which makes it easy to agglomerate in the coating and difficult to disperse evenly. At the same time, it improves the corrosion resistance of the resin itself in the coating. First, relying on the conductivity of graphene, the connection between zinc powder in the coating is enhanced, effectively extending the time that zinc powder provides cathodic protection; second, the corrosion resistance of the epoxy resin modified by graphene is enhanced.
[0079] The present invention provides a method for preparing the graphene-modified coating according to the above scheme, comprising the following steps:
[0080] Mixing a water-based epoxy curing agent, edge-oxidized graphene nanosheets, zinc powder, barium sulfate, a pigment, an alcohol solvent and a first auxiliary agent, and performing a first dispersion to obtain a dispersion material;
[0081] Sand-grinding the dispersed material to obtain component A;
[0082] Mixing a waterborne epoxy resin, water and a second auxiliary agent, and performing a second dispersion to obtain a B component;
[0083] The component A and the component B are mixed to obtain the graphene modified coating; the mass ratio of the component A to the component B is (3-5):1.
[0084] The invention mixes a water-based epoxy curing agent, edge oxide graphene nanosheets, zinc powder, barium sulfate, a pigment, an alcohol solvent and a first auxiliary agent, performs a first dispersion, and obtains a dispersion material.
[0085] In the present invention, the rotation speed of the first dispersion preferably starts from 300 r / min and gradually increases to 1500 r / min, more preferably adjusted at a speed of 100 r / min to 1500 r / min; then maintained at 1500 r / min for 30 to 60 min, more preferably 35 to 55 min, and more preferably 40 to 50 min.
[0086] After obtaining the dispersed material, the present invention performs sand milling on the dispersed material to obtain component A.
[0087] In the present invention, the sand grinding is preferably performed 1 to 2 times.
[0088] After the sand milling is completed, the obtained mixture is preferably passed through a 150-200 mesh sieve, and the number of sieving is preferably 1-2 times, and then weighed and packaged in sequence.
[0089] The present invention mixes water-based epoxy resin, water and a second auxiliary agent, performs a second dispersion, and obtains a B component.
[0090] In the present invention, the rotation speed of the second dispersion preferably starts from 200 r / min and gradually increases to 600 r / min, more preferably adjusted at a speed of 100 r / min to 600 r / min; then maintained at 600 r / min for 10 to 30 min, more preferably 15 to 25 min.
[0091] After obtaining the component A and the component B, the present invention mixes the component A and the component B to obtain the graphene-modified coating.
[0092] The present invention provides the use of the graphene-modified coating described in the above scheme or the graphene-modified coating prepared by the preparation method described in the above scheme in primer.
[0093] In the present invention, the application method preferably comprises: mixing the graphene modified coating with an inner paint to obtain a primer, and then sequentially brushing the primer, the middle paint and the outer paint on the substrate. In the present invention, the inner paint preferably comprises an epoxy inner paint; the middle paint preferably comprises an epoxy middle paint; and the outer paint preferably comprises an acrylic outer paint or a polyurethane outer paint.
[0094] The present invention preferably pre-treats the substrate before applying the primer. In the present invention, the pre-treatment preferably includes pickling or sandblasting. The present invention has no special requirements for the pickling and sandblasting methods, and methods well known in the art can be used. In the present invention, the pickling is specifically: alkaline washing and degreasing - water washing - pickling - water washing - drying; the sandblasting is specifically: using 3 to 6 Bar high-pressure air to drive metal abrasives (wire segments and steel shots with a particle size of ≤2mm) to impact the painted substrate to obtain a surface quality of Sa 2.5 (density 85%, roughness 25 to 50μ).
[0095] In order to further illustrate the present invention, a graphene-modified coating provided by the present invention and a preparation method and application thereof are described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0096] Example 1
[0097] A graphene modified coating, consisting of component A and component B; taking the mass of the graphene modified coating as 100%, the component A is:
[0098]
[0099] Taking the mass of the graphene modified coating as 100%, the component B is:
[0100]
[0101] Component A is as follows: the waterborne epoxy curing agent is a polyamide curing agent (Aradur 38-1 of Huntsman); the pigment is iron red; the cosolvent is butyl ether; and the anti-settling agent is fumed silica.
[0102] Component B is: the water-based epoxy resin is E20 water-based epoxy resin; the dispersant is BYK 190 dispersant; the wetting agent is BYK 349 wetting agent; the defoamer is BYK 024 defoamer; the pH adjuster is ammonia water, and the mass concentration of the ammonia water is 0.03%; the bactericide is Dow KATHON(TM) LXE Kathon; and the thickener is Dow RM-8W.
[0103] The preparation method of the edge oxide graphene nanosheet is:
[0104] After dissolving 9wt.% of the binder polyvinylidene fluoride (the mass of the binder is 9% of the mass of the single-layer graphene powder) in 5mL of N-methylpyrrolidone solution, 5g of the single-layer graphene powder was added to the above solution and mixed evenly using a homogenizer. The mixing speed was divided into three stages: the first stage was 300rpm for 60s; the second stage was 2000rpm for 600s; the third stage was 300rpm for 60s. The resulting mixture was then dried in a cubic mold at 70°C for 12h to obtain a graphene electrode sheet;
[0105] The graphene electrode sheet was subjected to low current density and ultra-low frequency alternating current electrolytic oxidation modification in an electrolytic cell for 24 hours, and the current density was 30 mA·cm -2 The frequency of the ultra-low frequency AC is 0.017 Hz, and the molar concentration of the electrolyte used in the electrolytic cell is 0.2 mol·L -1 A potassium bicarbonate solution is used to prepare a single-layer edge-oxidized graphene nanosheet, namely, an edge-oxidized graphene nanosheet.
[0106] The preparation method of component A is as follows: a water-based epoxy curing agent, edge oxide graphene nanosheets, zinc powder, barium sulfate, pigment, alcohol solvent, cosolvent and dust-proof agent are weighed according to the above weight parts, and the materials are added into a premixing tank one by one for dispersion. The speed of the disperser is adjusted from 300 r / min, and the speed is gradually increased by 100 r / min until the speed reaches 1500 r / min, and then maintained at 1500 r / min for 60 minutes to obtain a mixture;
[0107] The mixture is put into a sand mill and sand-milled for 2 times, the water-cooled temperature of the sand mill is controlled below 60° C., and then filtered through 150 meshes for 2 times, and weighed and packaged in sequence to obtain a sand mill material;
[0108] The preparation method of component B is as follows: water-based epoxy resin, water, dispersant, wetting agent, defoamer, pH regulator, bactericide and thickener are weighed according to the above weight parts, and added into the premixing tank one by one for dispersion. The speed of the disperser is adjusted from 200 r / min, and gradually increased by 100 r / min until the speed reaches 600 r / min, and then maintained at 600 r / min for 30 min, and then weighed and packaged in sequence to obtain a mixture.
[0109] The prepared component A and component B are mixed to obtain a graphene-modified coating.
[0110] Performance Testing
[0111] Comparative testing of the anti-corrosion performance of primers with different zinc powder ratios.
[0112] 1. Test materials:
[0113] 1. Steel plate: size: 1.6mm×100mm×50mm; surface condition: sandblasted and rust-removed, density 85%, roughness 25~50μ; quantity: 11 pieces;
[0114] 2. Paint package: primer 30μ + intermediate paint 40μ + top coat 40μ;
[0115] 2. Testing tools: salt spray test chamber;
[0116] 3. Experimental unit: Laboratory of College of Chemistry and Environmental Engineering, Shenzhen University;
[0117] 4. Test methods:
[0118] 1. Test board production:
[0119] (1) Preparation of primer: Mix zinc-rich paint (graphene-modified paint prepared by the present invention) and interior paint in a certain ratio (see Figures 1-2 ) for mixing, Figures 1-2 The mixing ratio refers to the content of graphene modified coating (zinc-rich paint) in the primer.
[0120] (2) Primer brushing: Apply the mixed primer on the test panel by brushing.
[0121] (3) Spraying of intermediate paint and outer paint: When the test plate coated with primer reaches surface dryness, the intermediate paint can be sprayed. After leveling for 10 minutes, the outer paint is sprayed, and the total thickness is controlled at 120 μm. This embodiment uses HEMPEL brand paint products, inner paint 45200, intermediate paint 15300, and outer paint 56430.
[0122] (4) Drying the test panel: Place the painted test panel in a drying room and bake it at 60°C for 30 minutes. Take it out and let it cool to below 40°C.
[0123] 2. Salt spray test:
[0124] Place the test sample in a salt spray test chamber for corrosion resistance testing (according to ASTM B117 standard), and record the test data, including rust level, blister level (compare the results according to the standard drawings), and acceleration line conditions. Figures 1-2 .
[0125] V. Experimental analysis:
[0126] According to the test data, the anti-corrosion performance of the primer test panels with different zinc powder ratios was analyzed.
[0127] Figures 1-2 Table 1 shows the anti-corrosion performance results of primers with different zinc powder ratios at test times of 120h and 240h ( Figures 1-2 The figures in the figure correspond to the data in Table 1 one by one). Figures 1-2 The left side in the middle are all test result graphs for 120 hours, and the right side are all test result graphs for 240 hours. From top to bottom, they are the test result graphs when the zinc-rich paint content in the primer is 100wt.%, 90wt.%, 80wt.%, 70wt.%, 60wt.%, 50wt.%, 40wt.%, 30wt.%, 20wt.%, 10wt.%, and 0wt.%.
[0128] Table 1 Anticorrosion performance results of primers with different zinc powder ratios at test times of 120h and 240h
[0129]
[0130]
[0131] Figures 3-4 Table 2 and Table 3 show the anti-corrosion performance results of primers with different zinc powder ratios at test times of 480h and 720h. Figures 3-4 The graphs in Figure 2 correspond to the data in Table 2). Figures 3-4 The left side in the middle are all test result graphs for 480 hours, and the right side are all test result graphs for 720 hours. From top to bottom, they are the test result graphs when the zinc-rich paint content in the primer is 100wt.%, 90wt.%, 80wt.%, 70wt.%, 60wt.%, 50wt.%, 40wt.%, 30wt.%, 20wt.%, 10wt.%, and 0wt.%.
[0132] Table 2 Anticorrosion performance results of primers with different zinc powder ratios at test times of 480h and 720h
[0133]
[0134]
[0135] from Figures 1 to 4 As shown in Tables 1 and 2, with the decrease of zinc powder ratio, the anti-corrosion performance of the sample coating shows a gradual downward trend.
[0136] Figure 5 The salt spray comparison test chart of the pickled plate and the sandblasted plate when the test time was 120h, 240h, 480h and 720h respectively. Figure 5The left side is the sandblasting plate, and the right side is the pickling plate, which correspond to the test time of 120h, 240h, 480h and 720h from top to bottom. The steel plate is pre-treated, and the pre-treatment is divided into pickling and sandblasting. The specific process of pickling is: alkaline washing and degreasing - water washing - pickling (using hydrochloric acid with a mass concentration of 15%) - water washing - drying. Sandblasting: Use 3-6Bar high-pressure air to drive metal abrasives (the particle size of steel wire segments and steel shots is 2mm, and the mass ratio of steel wire segments to steel shots = 3:7) to impact the coating substrate to obtain Sa2.5 surface quality (density 85%, roughness 25-50μ).
[0137] from Figure 5 It can be seen that the sample treated with sandblasting is worse than the sample treated with pickling in terms of accelerated linear etching. The reason is that the pickling treatment can remove the oxide scale on the surface of the sample more thoroughly.
[0138] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A graphene-modified coating, characterized in that: It includes component A and component B; Taking the mass of the graphene modified coating as 100%, the component A comprises: Taking the mass of the graphene modified coating as 100%, the component B comprises: Water-based epoxy resin 15-20%; Water 1-3%; The second auxiliary agent is 1.19-2.7%; The mass ratio of component A to component B is (3-5):
1.
2. The graphene-modified coating according to claim 1, characterized in that: The method for preparing the edge oxide graphene nanosheets comprises the following steps: Mixing a binder, an organic solvent and a single-layer graphene to prepare a graphene electrode sheet; The graphene electrode sheet is subjected to electrolytic oxidation modification to obtain the edge oxide graphene nanosheet.
3. The graphene modified coating according to claim 1 or 2, characterized in that: Taking the mass of the graphene modified coating as 100%, the first auxiliary agent includes 5-10% of the auxiliary solvent and 0.5-1.5% of the anti-settling agent; the total mass of the alcohol solvent and the first auxiliary agent is 9.5-20%.
4. The graphene-modified coating according to claim 1, characterized in that: Taking the mass of the graphene modified coating as 100%, the second auxiliary agent includes 0.5-1% of a dispersant, 0.5-1% of a wetting agent, 0.1-0.5% of a defoaming agent, 0.02-0.05% of a pH regulator, 0.02-0.05% of a bactericide, and 0.05-0.1% of a thickener.
5. The graphene-modified coating according to claim 1 or 4, characterized in that: The total mass of the water and the second auxiliary agent is 2.29-5%.
6. The graphene-modified coating according to claim 1, characterized in that: The waterborne epoxy curing agent includes a polyamide curing agent and / or a fatty amine curing agent; the waterborne epoxy resin includes E20 waterborne epoxy resin.
7. The method for preparing the graphene-modified coating according to any one of claims 1 to 6, characterized in that: The following steps are involved: Mixing a water-based epoxy curing agent, edge-oxidized graphene nanosheets, zinc powder, barium sulfate, a pigment, an alcohol solvent and a first auxiliary agent, and performing a first dispersion to obtain a dispersion material; Sand-grinding the dispersed material to obtain component A; Mixing the waterborne epoxy resin, water and the second auxiliary agent, performing a second dispersion, and obtaining component B; The component A and the component B are mixed to obtain the graphene modified coating; the mass ratio of the component A to the component B is (3-5):
1.
8. The preparation method according to claim 7, characterized in that: The rotation speed of the first dispersion starts from 300 r / min, gradually increases to 1500 r / min, and then is maintained at 1500 r / min for 30 to 60 min.
9. The preparation method according to claim 7 or 8, characterized in that: The rotation speed of the second dispersion starts from 200 r / min, gradually increases to 600 r / min, and then is maintained at 600 r / min for 10 to 30 min.
10. Use of the graphene-modified coating according to any one of claims 1 to 6 or the graphene-modified coating prepared by the preparation method according to any one of claims 7 to 9 in primer.
Citation Information
Patent Citations
Long-acting anti-corrosion graphene modified waterborne epoxy zinc-rich primer and preparation method thereof
CN115466554A
Single-layer edge graphene oxide and preparation method thereof
CN116514114A